Percepções de professoras de escolade públicas eucação infantil acerca de sua formação e prática educativa: o caso de Medianeira - PR - De Marco, Marilete Terezinha [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work aims to share the performed studies in a Master´s degree research at the Pos Graduation Program in Education of Unesp, Campus Marilia, São Paulo. As the main objective of these studies, it was delimited to check the perceptions of the Infant Education teachers about the (des) compasses between their initial and continuous formation and their practice effectively performed. Our investigation problem was: what are the perceptions of the Infant Education public school teachers of Medianeira, Paraná, about their initial and continuous formation? The theoretical fundamentals used during the literature review focused, especially at the studies on the Historical-Cultural Theory. We also bring other contemporary authors to highlight the teacher´s training value with the child´s work and the impacts of the learning arising from this formation for their pedagogical practices. As a tool of data production, we use the semi-structured interview with eight child´s teachers and the observation of two pedagogical situation of each one of them. By the researched teachers´ reports and the observed pedagogical situations during the investigation, we understand that the teacher´s training courses still do not attend the contents considered essentials for the good teacher´s practice. We defend that the teacher´s training focused to the Infant Education must privilege knowledge from different areas that are capable to guide pedagogical actions focused to the full child´s development, searching for the effectiveness of their multiple possibilities and the learning capacity. In this perspective, the Infant Education teacher´s training process covers the constitution of essential knowledge to a humanizing education, that during childhood means to educate caring and to care educating, recognizing the individual needs and respecting the child social, historical and cultural differences

A presente dissertação visa compartilhar os estudos realizados em pesquisa de Mestrado junto ao Programa de Pós-Graduação em Educação da Unesp, Campus de Marília, São Paulo. Foi delimitado como o objetivo principal destes estudos, verificar nas percepções de professoras de Educação Infantil acerca dos (des) compassos entre sua formação inicial e continuada e sua prática efetivamente realizada. Nosso problema de investigação foi: quais as percepções de professoras de escolas públicas de Educação Infantil de Medianeira/Paraná, acerca de sua formação inicial e continuada? A base teórica utilizada para a revisão bibliográfica voltou-se, especialmente, para os estudos da Teoria Histórico-Cultural. Também trouxemos outros autores contemporâneos que destacam o valor da formação docente no trabalho com a criança pequena e os impactos das aprendizagens decorrentes dessa formação para suas práticas pedagógicas. Como instrumento de produção dos dados, realizamos entrevista semiestruturada com oito professoras de Educação Infantil e a observação de duas situações pedagógicas de cada uma delas. Por meio dos relatos das professoras investigadas e das situações pedagógicas observadas durante a investigação, compreendemos que os cursos de formação de professoras ainda não contemplam os conteúdos considerados essenciais para uma prática docente a favor das especificidades da criança. Defendemos que a formação docente voltada à Educação Infantil deve privilegiar conhecimentos de diferentes áreas capazes de orientar ações pedagógicas voltadas ao pleno desenvolvimento da criança, buscando a efetivação de suas múltiplas possibilidades e capacidade para aprender. Sob esta perspectiva, o processo de formação de professoras de Educação Infantil abrange a constituição de conhecimentos imprescindíveis a uma educação humanizadora que, na infância, envolve educar cuidando e cuidar educando...
Keywords: Educação de crianças; Professores - Formação; Educação - Paraná; Educação permanente; Teachers, Training of